Challenges for child support schemes: Accounting for shared care and complex families. (July 2018) - Claessens, Elke; Mortelmans, Dimitri
The increasing prevalence of shared care and complex families is challenging traditional approaches to child support determination based on the 'classic' two-parent, sole custody, post-divorce family. This article provides a comparative analysis of how these challenges are being addressed in the child support schemes of eight different countries and evaluates these approaches in the light of family policies on gender equality in family care. We find great diversity in the incorporation of shared care and complex families, which is not clearly connected to existing ideal typical policy models on gendered family care. However, child support schemes, at least partially, seem to translate into assumptions concerning gender roles and general policy aims concerning gender equality. In order to better understand how countries accommodate the challenges arising from the modern post-separation family, gender equality seems a vital consideration to take into account.